2018
DOI: 10.3390/s18093100
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study on Timber Moisture Monitoring Using Piezoceramic Transducer-Enabled Active Sensing

Abstract: In recent years, the piezoceramic transducer-enabled active sensing technique has been extensively applied to structural damage detection and health monitoring, in civil engineering. Being abundant and renewable, timber has been widely used as a building material in many countries. However, one of the more challenging applications of timber, in construction, is the potential damage caused by moisture. Increased moisture may cause easier warping of timber components and encourage corrosion of integrated metal m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 78 publications
0
17
0
Order By: Relevance
“…Furthermore, because of its strong piezoelectric effect [40,41] and wide bandwidth [42,43,44], Lead Zirconate Titanate (PZT) is one of the most commonly used piezoceramic materials, and is frequently utilized for stress wave generation [45,46,47,48] and detection [49,50,51]. Stress waves are often used in structural health monitoring [52,53,54,55,56], especially in the active sensing method [57,58,59,60,61] and the electromechanical impedance method [62,63,64,65,66]. The active sensing method was used for monitoring bolt loosening [58], very early age cement hydration [59], a bolted spherical joint connection [60], and timber moisture [61].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, because of its strong piezoelectric effect [40,41] and wide bandwidth [42,43,44], Lead Zirconate Titanate (PZT) is one of the most commonly used piezoceramic materials, and is frequently utilized for stress wave generation [45,46,47,48] and detection [49,50,51]. Stress waves are often used in structural health monitoring [52,53,54,55,56], especially in the active sensing method [57,58,59,60,61] and the electromechanical impedance method [62,63,64,65,66]. The active sensing method was used for monitoring bolt loosening [58], very early age cement hydration [59], a bolted spherical joint connection [60], and timber moisture [61].…”
Section: Introductionmentioning
confidence: 99%
“…Stress waves are often used in structural health monitoring [52,53,54,55,56], especially in the active sensing method [57,58,59,60,61] and the electromechanical impedance method [62,63,64,65,66]. The active sensing method was used for monitoring bolt loosening [58], very early age cement hydration [59], a bolted spherical joint connection [60], and timber moisture [61]. The impedance method was used for monitoring the damage in plate-like structures [62], bolted joint looseness [63], pin connection loosening [64], the freeze–thaw process in soil [65], and a concrete-filled fiber-reinforced polymer tube [66].…”
Section: Introductionmentioning
confidence: 99%
“…Two PZT patches will be strategically placed across the potential location. The so-called active sensing method [71][72][73][74] will be adopted to monitor the cracks. In the active sensing approach, one PZT patch will be used to generate a stress wave that can propagate along a structure, and another PZT patch can also be used as a sensor to detect the stress wave.…”
Section: Discussion On Real-time Damage Monitoringmentioning
confidence: 99%
“…The piezoelectric transducer-based active sensing method combined with wavelet packet analysis was used by Yang W (2018) [52] to monitor the soil compactness, the results showed that the method can effectively identify the soil compaction degree. [53,54] detected the damage and moisture of timber by using PZT transducer-based active sensing, the results showed that the active monitoring method based on piezoelectric transducer can better identify the damage level and the moisture change of wood.…”
Section: Introductionmentioning
confidence: 99%